To kill a black swan : the credibility revolution at CEDE, 2000-2018 (2020)
The growing displacement of theory and other forms of wide-ranging knowledge of social phenomena by empirical research methods in economics is widely noted by economists and historians of economic knowledge. Less attention has been devoted, however, to understand the materialization of such changes in the scientific practices in a specific research center. This article studies the recent transformations in the epistemological practices at CEDE, a research center that is both, highly influential in the production of economic knowledge in Colombia, and does not belong to the core economics research centers that lead the debates regarding the recent changes in the discipline. I use a machine learning technique called Topic Modeling, interviews to CEDE researchers, and exegesis of papers to identify a shift in the production of knowledge in microeconometrics at CEDE during the years 2000 and 2018. I explain this shift by characterizing two sets of epistemological practices. The first one, usually present during the years 2000 and 2006, establishes a complementary relationship between wide-ranging knowledge (theory included) and data estimation techniques in order to achieve a broad comprehension of the phenomenon under study. The second one, usually present during the years 2009 and 2018, prioritizes data estimation techniques over theoretical models and contextual knowledge in order to achieve a causal comprehension of one variable in the phenomenon under study. Because epistemological practices make truth claims, each one establishes its own criteria about what constitutes a valid research through a distinct way of replicating a scientific experiment. The shift I identify implies a recent tendency to disdain research works that cannot make a strong causal inference.